All forecasters are not the same: Systematic patterns in predictive performance - Robert W. Rich; Joseph S. Tracy (American Enterprise Institute (AEI), 2024)
Are all forecasters the same? Expectations models incorporating information rigidities typically imply forecasters are interchangeable which predicts an absence of systematic patterns in individual forecast behavior. Motivated by this prediction, we examine the European Central Bank's Survey of Professional Forecasters and find, in contrast, that participants display systematic patterns in predictive performance both within and across target variables. Moreover, we document a new result from professional forecast surveys which is that inter- and intra-forecaster relative predictive performance are strongly linked to the degree of difficulty in the forecasting environment. This insight can inform the ongoing development of expectations models.
Keywords: 330; forecasting profession; surveys; evaluating forecasts; point forecasts; density forecasts; heterogeneity